The Nature of Auditory Linguistic Input in the Curriculum and its Role in Developing Linguistic and Communicative Competence at the Primary Stage (The International Journal for Scientific Research, 2024)
This study aims, on one hand, to discuss the auditory linguistic input in the curriculum of the Arabic language subject and highlight its role in building linguistic and communicative proficiency at the elementary educational level. The issue of linguistic input, which learners of a second language should be exposed to, still raises deep questions regarding its nature, quality, and the necessary amount to be adopted for the development of linguistic competencies and communication skills in Arabic. On the other hand, it seeks to discuss the hypotheses put forward regarding the teaching of listening and speaking skills to learners at the elementary educational level, and their role in the child's acquisition of the second language in a natural manner.
Keywords: Auditory Linguistic Income; Linguistic and Communicative Competence; Listening and Speaking Skills